Research and practice of mobile application lifecycle management platform - Ming YIN; Lin LI (Dianxin kexue)
According to the development status of various security services for mobile applications,the mainstream mobile application security detection and monitoring technology was studied.Based on the concept of full life cycle management in software industry,a variety of security concepts and security technologies were reasonably integrated into each stage of the whole life cycle of mobile applications.Based on this,a mobile application lifecycle management platform with comprehensive security functions and multi system cooperation was designed and constructed.